2010
DOI: 10.1074/jbc.m110.107219
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Multifarious Horizontal Transfer of an Alternative Biosynthetic Pathway for the Alternative Polyamine sym-Homospermidine

Abstract: Polyamines are small flexible organic polycations found in almost all cells. They likely existed in the last universal common ancestor of all extant life, and yet relatively little is understood about their biological function, especially in bacteria and archaea. Unlike eukaryotes, where the predominant polyamine is spermidine, bacteria may contain instead an alternative polyamine, sym-homospermidine. We demonstrate that homospermidine synthase (HSS) has evolved vertically, primarily in the ␣-Proteobacteria, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 78 publications
2
69
0
Order By: Relevance
“…The ability of sym-homospermidine to replace spermidine in C. jejuni, and of N 1 -aminopropylcadaverine to replace spermidine in E. coli, indicates that the exact structure of the polyamine is not critical. Indeed, in most species in the bacterial phyla Chlorobi and Chloroflexi, in filamentous Cyanobacteria, and in many ␣-proteobacteria, symhomospermidine is the only polyamine present (6). Although sym-homospermidine and N 1 -aminopropylcadaverine are one carbon longer than spermidine, they are flexible linear chains and can bend, whereas sym-norspermidine, which is one carbon shorter than spermidine, is unlikely to stretch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of sym-homospermidine to replace spermidine in C. jejuni, and of N 1 -aminopropylcadaverine to replace spermidine in E. coli, indicates that the exact structure of the polyamine is not critical. Indeed, in most species in the bacterial phyla Chlorobi and Chloroflexi, in filamentous Cyanobacteria, and in many ␣-proteobacteria, symhomospermidine is the only polyamine present (6). Although sym-homospermidine and N 1 -aminopropylcadaverine are one carbon longer than spermidine, they are flexible linear chains and can bend, whereas sym-norspermidine, which is one carbon shorter than spermidine, is unlikely to stretch.…”
Section: Discussionmentioning
confidence: 99%
“…The Pseudomonas aeruginosa PAO1 N-carbamoylputrescine amidohydrolase gene deletion produced a leaky biosynthetic phenotype, and it was consequently found that acetylputrescine amidohydrolase, which has a very similar substrate to N-carbamoylputrescine (26), is induced in the gene deletion mutant and allows bypass of the metabolic block. The CANSDH/ CASDH enzyme is related to homospermidine synthase, lysine 6-dehydrogenase, saccharopine dehydrogenase, and aspartate dehydrogenase (6). There may be a dehydrogenase in C. jejuni that can serendipitously substitute the activity of the missing CASDH.…”
Section: Discussionmentioning
confidence: 99%
“…In homospermidine-producing bacteria, a bacterial HSS (EC 2.5.1.44) catalyzes the formation of homospermidine from two molecules of putrescine in an NAD + -dependent reaction (33,34). Despite the similar reaction mechanism, bacterial HSS and plant-derived HSS are not related with respect to the degree of sequence identity (12,35) and to their predicted 3D structure (24). Both the presence of introns at conserved positions in the genomic DNA encoding the HSS identified in C. spectabilis, and the ability of this enzyme to catalyze the formation of homospermidine from spermidine and putrescine, establishes that the identified HSS is not of bacterial, but of plant, origin.…”
Section: Discussionmentioning
confidence: 99%
“…A central question in our study has been which partner of the symbiosis provides homospermidine for PA biosynthesis: the microsymbiont or the plant. In many bacterial phyla, homospermidine is found to replace spermidine, which is the prevalent triamine in other bacteria and in eukaryotes (24). Indeed, homospermidine has been found repeatedly in nodules of fabaceous plants and in the associated rhizobia (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation